Fault Analysis and Handling in Low-Voltage Networks at PT. PLN (Persero) UP3 Sidoarjo ULP Krian - Ibrohim, Ibrohim; Muhammad Roihan Amir (Indonesian Journal of Engineering and Technology (INAJET), 2025)
Low-voltage electricity distribution networks have an important role in ensuring a reliable electricity supply for the community because they are directly connected to customers. However, this network is prone to disturbances due to natural factors such as extreme weather and external disturbances such as fallen trees, wild animals, and human activities. This study aims to identify the types of disorders that commonly occur and evaluate the effectiveness of the handling procedures implemented by PT PLN (Persero) UP3 Sidoarjo ULP Krian. The method used is qualitative descriptive through direct observation in the field with the PLN technical team. The results of the study showed that the most dominant disturbances were caused by strong winds, heavy rain, and cable connection disruptions. Handling procedures start from identifying the location of the fault through customer reports, technical checks using measuring instruments such as ampere pliers and tespen, to corrective actions and evaluations. In addition, the aspect of occupational safety is also a major concern in each stage. Evaluation of the system is carried out post-repair to ensure there is no potential for further disruption. In conclusion, the reliability of the distribution network can be improved through systematic handling procedures, periodic maintenance, and active participation of the community. This study provides a practical overview of the importance of network disruption management as part of efforts to improve the quality of national electricity services.  Keywords: Power outage, Distribution network, System reliability, Technical handling